RISK ASSESSMENT OF ACUTE POSTMANIPULATED PANCREATITIS IN THE PERFORMANCE OF INTRAOPROPOSITION ANTERGRADE ENDOSCOPIC PAPILLOSPHINCTEROMY - Снигирев, Алексей Юрьевич; Алексеев, Николай Анатольевич; Снигирев, Юрий Владимирович; Баранов, Андрей Игоревич (Medicine in Kuzbass, 2019)
Abstract. Retrospective analysis of surgical treatment of complicated cholelithiasis with the use of intraoperative antegrade endoscopic papillosphincterotomy (IAEPST) in 438 patients admitted for the period from 2010 to 2017. In a planned order, 325 patients (74.2 %) were admitted, in an emergency 113 patients (25.8 %). The age of patients ranged from 18 to 87 years. Objective. Assess the risk of developing acute post-manipulation pancreatitis when performing an IAEPST in groups of planned and emergency patients. Methods. The IAEPST was performed by an antegrade technique with a tension-type papillotome institution through the cystic duct and removing its working part through the mouth of the large duodenal papilla. Papillotom was installed in the working position for 11 hours and papillotomy was performed. In the subsequent papillotom, the bile duct was removed and performed a Dormia basket or balloon catheter. Results. In the group of planned patients, laparoscopic cholecystectomy in combination with IAEPST was performed in 318 patients (97.8 %). In 5 cases (1.5 %), a conversion was performed for laparotomic access. From minilaparotomic access cholecystectomy with an IAEPST was performed in 2 patients (0.7 %). In the group of emergency patients, laparoscopic cholecystectomy in combination with IAEPST was performed in 97 patients (85.8 %). From minilaparotomy access, treatment was performed in 1 patient (0.9 %). Laparotomic access was applied in 15 patients (13.3 %). The percentage of acute post-manipulation development in both groups was 0.75 %, no statistically significant differences in both groups (p > 0,1) were found. Conclusion. The incidence of acute post-manipulation pancreatitis with the use of an IAEPST is 0.75 %. The use of an IAEPST is an effective alternative to the retrograde method of reducing the number of post-manipulation complications.